Environmental taxation, tax competition, and harmonization - Cremer, Helmuth; Gahvari, Firouz (2004)
This paper studies the tax competition problem in the presence of transboundary pollution. It shows that economic integration causes the firms to adopt the same or less polluting technologies, but it nevertheless increases aggregate emissions and lowers welfare. Second, the paper examines the ramifications of partial tax harmonization policies. It shows that harmonizing commodity taxes above their unrestricted Nash equilibrium value may either increase or lower the equilibrium emission tax. Under the former, firms opt for less polluting technologies, aggregate emissions decrease and welfare improves. On the other hand, if emission tax goes down, firms will choose more polluting technologies, aggregate emissions will increase and welfare deteriorates. Finally, harmonizing the emission tax above its unrestricted Nash equilibrium value, which leads the firms to adopt a less polluting technology, also causes aggregate emissions to decline and overall welfare to increase. - Reproduced.
Keywords: Environment; Taxation